TOURISM AND AGRICULTURE: A MODEL OF “SLOW FOOD” TO PROMOTE LOCAL AGRARIAN PRODUCTS THROUGHOUT TOURISM TO ASSIST THE POOR IN LATIN AMERICA - Murphy, Kevin (2012)
Tourins in creasingly plays a very important roll on tha globals economy of the diferent sectors that developed it and is now widely recognized as one of the major industries of the world, thats why tourism potential i son the promotion of one positive economic impact for the diferent sectors that are aimed, that`s why this article pretends to propose how thae promotion of local agricultural products can be assisted with the implementation of a model of “slow nutrition” that can be developed by tourisn sector on behalf of the unfortunate sector of Latinoamerica.